ORGANIZATIONAL CULTURE AND ITS RELATIONSHIP WITH THE FUNCTIONAL SIMILARITY OF TEACHING STAFF AT DHIQAR UNIVERSITY - Lecturer Dr. Jasim Saad Jasim (Scholars Digest Publishing, 2024)
The main problem of the research is not in the existence of the two variables of organizational culture and organizational symmetry or not, because they are present at Dhi Qar university, but the problem is in not understanding them as a term that exists and is circulating in most other fields and therefore overlooking their role, and in order to put them in their right place, realize, apply and employ them correctly in a way that reflects on the loyalty of teachers and their affiliation and achieving the required change at the level of their performance and behavior, and the aim of this research is to study the influential relationship of organizational culture in the crystallization of organizational symmetry and measuring their level, and conducting research on teachers at the presidency of Dhi Qar University who were deliberately selected, where were distribute A questionnaire designed by the researcher and after analyzing the results, it turned out that the level of organizational culture and organizational similarity is high and that there is an impact of organizational culture at the level of similarity ( match ) of the individual with his organization as a result of the similarity of the values and beliefs of the University with the values and beliefs of performance by finding factors Adaptation of teaching to both internal and external environment.
Keywords: Organizational Culture; functional similarity